The Bank of the State of Missouri - Cable, John Ray (Studies in History, Economics, and Public Law, 1969)
Studies the economics of the state of Missouri beginning in the early 1800's. Looks at the founding of the Bank of the State of Missouri in 1837 through its assimilation and nationalization in 1866